Fatty Acid Accumulations and Transcriptome Analyses Under Different Treatments in a Model Microalga Euglena gracilis - He, Jiayi; Du, Ming; Chen, Yehua; Liu, Yerong; Zhang, Jinlin (Kenny); Fu, Wen; Lei, Anping; Wang, Jiangxin (Frontiers in Chemical Engineering, 2022)
With the continuous growth of the world's population and the increasing development of industrialization, the demand for energy by human beings has been expanding, resulting in an increasingly severe energy crisis. Microalgae are considered the most potential alternatives to traditional fossil fuels due to their many advantages, like fast growth rate, strong carbon sequestration capacity, and low growth environment requirements. For heterotrophic growth, Euglena can also use carbon sources such as glucose, ethanol, and others. What’s more, Euglena is highly adaptable to the environment and has a high tolerance to various environmental stresses, such as salinity, heavy metals, antibiotics, etc. Different treatments of Euglena cells could affect their growth and the accumulation of bioactive substances, especially fatty acids. To expand the industrial application of Euglena as a potential biodiesel candidate, we aim to determine the environmental stresses (antibiotics, heavy metals, salinity) or carbon resources (glucose and ethanol) the potential for higher quality and yield of fatty acid yield with a high growth rate. Adding glucose in the culture media increases cell biomass and fatty acid production with high-quality biodiesel characters. The transcriptome analysis helped explore the possible regulation and biosynthesis of fatty acids under different treatments and exploited in the improvement of biodiesel production. This study provides new insights for further improvement and various culture treatments Euglena-based biodiesel and jet fuels.